PELATIHAN PEMBUATAN DAN PENGGUNAAN GOOGLE MAPS KEPADA SISWA DAN SISWI SMP MUHAMMADIYAH PARAKAN - Ade Maulana; Alifiana Safitri; Allyssa Zahra Azizah Salsabilla; Gustyaanto Firgiawan; Muyassar Ahmad Taqy; Naufal Febrian; Nazwa Lintang Seina; Slamet Supriyadi; Topan Padilla Malik; Veny Masullah; Iis Aisyah (Abdi Jurnal Publikasi, 2023)
This training aims to provide further understanding regarding the use of Google Maps. With the increasingly rapid development of technology, namely map-based applications, there are many features in Google Maps, namely, location search, users can search for specific locations, as well as addresses, businesses, restaurants and other interesting places. However, in this research we prioritize the feature for determining a location, which is a feature that is used to determine a specific location, usually this feature is mostly used by someone who has a business or who is going to start a business and can also be used for the house itself. It is hoped that this feature can be used effectively.